Sustained Visual Attention Performance-Associated Prefrontal Neuronal Activity: Evidence for Cholinergic Modulation - Gill, T. Michael (J Neurosci, 2000)
Cortical cholinergic inputs are hypothesized to mediate attentional functions. The present experiment was designed to determine the single unit activity of neurons within the medial prefrontal cortex (mPFC) of rats performing a sustained visual attention task. Demands on attentional performance were varied by the presentation of a visual distractor. The contribution of cholinergic afferents of the mPFC to performance-associated unit activity within this area was determined by recording neuronal activity before and after unilateral cholinergic deafferentation using intracortical infusion of the immunotoxin 192 IgG-saporin. Presentation of the visual distractor resulted in a decrease in the detection of brief, unpredictable visual signals. As predicted, the unilateral loss of cholinergic inputs within the recording area of the mPFC did not affect sustained attentional performance. Cholinergic deafferentation, however, resulted in a decrease in the overall firing rate of medial prefrontal neurons and a substantial reduction in the proportion of neurons whose firing patterns correlated with specific aspects of behavioral performance. Furthermore, cholinergic deafferentation attenuated the frequency and amplitude of increased mPFC neuronal firing rates that were associated with the presentation of the visual distractor. The main findings from this experiment suggest that cholinergic inputs to the mPFC strongly influence spontaneous and behaviorally correlated single unit activity and mediate increases in neuronal activity associated with enhanced demands for attentional processing, all of which may be fundamental aspects in the maintenance of attentional performance.